Impact of Seed Priming on Germination, Growth, Flowering and Yield of Gaillardia pulchella var. Lorenziana - Poornima, D. M.; Prashantha , V.; Ambrish, S.; Polara, N. D. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during rainy season 2021–22 at the Department of Floriculture and Landscape Architecture, Junagadh Agricultural University, Gujarat, to evaluate the influence of different seed-priming treatments on germination, growth, and yield of Gaillardia. Gaillardia pulchella var. Lorenziana (blanket flower) is an important ornamental species valued for its vivid blooms and use in landscaping and cut flower arrangements, yet its cultivation has often been limited by poor germination and low yield. Seed priming is recognized as a simple and economical approach to overcoming poor seed performance, and the present study assessed the effects of potassium nitrate (KNO3), gibberellic acid (GA3), and Trichoderma harzianum under field conditions. Priming with 0.3% KNO3 proved most effective, recording the earliest germination (5.58 days), the highest germination percentage (99.3%), and the greatest seedling vigor index (670.28). This treatment also significantly improved stem diameter, branching, floral traits, and yield (15.22 t ha-1). Priming with GA3 at 100 ppm enhanced plant height (81.68 cm) and leaf area (72.93 cm²), reflecting its promotive role in vegetative growth. Although T. harzianum showed moderate improvements, its effects were comparatively lower than chemical priming. Overall, 0.3% KNO3 priming emerged as a practical and cost-effective technology for enhancing seed performance and productivity in Gaillardia, while GA3 supplementation was beneficial for promoting vegetative development. These findings provide a scientifically validated strategy for improving Gaillardia cultivation and nursery management.